Pervasive Computing for Collaborative Education - Erwin S Panjaitan; Rahmat Budiarto; Abdul Wadud Ismail (Jurnal SIFO Mikroskil, 2011)
Computing is becoming a part of our daily life and so is the Internet. Pervasive computing aims to make our lives simpler by using the tools which will allow us to serve the Internet and enable us to gain information easily. The tools as mentioned earlier are portable devices which allow any users to plug into powerful networks. These devices are no longer restricted to computers alone as understood previously This article is written based on research conducted concerning the advantages and disadvantages of pervasive computing to university students in Malaysia and the problems faced by students and their solutions. We propose that pervasive computing should be implemented and used in the high education. The younger generations should be exposed widely to the high technology in order to strive and succeed the challenges in progressive world. Through the Internet, the users will also be more familiar to the World Wide Web and thus gaining more benefits in their education line.